Comparison of cardiovascular outcomes and all-cause mortality in patients with chronic hepatitis B and C: A 13-year nationwide population-based study in Asia. (February 2018) - Wu, Victor Chien-Chia; Chen, Tien-Hsing; Wu, Michael; Cheng, Chun-Wen; Chen, Shao-Wei; Chang, Chun-Wei; Chen, Ching-Chang; Chang, Shang-Hung; Hung, Kuo-Chun; Chern, Ming-Shyan; Lin, Fen-Chiung; Chu, Pao-Hsien; et al.
Abstract: Background and aims: Viral hepatitis infection has been linked to increased atherosclerosis. We therefore investigated cardiovascular outcomes in patients with hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Methods: Electronic medical records during 2000–2012 were retrieved from the Taiwan National Health Insurance Research Database. Exclusion criteria were age <18, history of coexisting HBV and HCV infection, acute coronary syndrome, coronary intervention, venous thromboembolism, peripheral artery disease, stroke, major or gastrointestinal bleeding, malignancy, and a follow-up period <180 days. Patients with HBV and HCV infection were propensity-matched then compared for outcomes. Primary outcomes were cardiovascular events at the 1-year follow-up, 3-year follow-up, 5-year follow-up, and at the end of follow-up. Results: 41, 554 patients with diagnosis of HBV or HCV were retrieved from 2000 to 2012. After exclusion criteria, 31, 943 patients were eligible for analysis and propensity score matched. The study population consisted of 6030 patients with HBV infection and 6030 patients with HCV infection. Risk of composite arterial events (acute coronary syndrome, peripheral artery disease, and acute ischemic stroke) was significantly higher in patients with HCV infection compared with patients with HBV infection ( p  = 0.012 at 5-year follow-up and p  = 0.003 at the end of follow-up). All-cause mortality was significantly higher in patients with HCV infection compared with patients with HBV infection ( p  < 0.001 at 3-year follow-up, 5-year follow-up, and at the end of follow-up). Conclusions: In patients with chronic viral hepatitis, subjects with HCV infection had a significantly higher risk of composite arterial events and all-cause mortality compared with those with HBV infection. Highlights: Viral infections have been linked to atherosclerosis and cardiovascular events. Inconsistent study results reported regarding the atherosclerotic potential by viral hepatitis B and C. There exist no direct comparison for the effect of viral hepatitis B and C on atherosclerosis. Patients with HCV had significantly increased risks in cardiovascular events compared to patients with HBV.